2023
DOI: 10.1038/s41477-023-01391-3
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin and abscisic acid transporters facilitate endodermal suberin formation in Arabidopsis

Abstract: The plant hormone gibberellin (GA) regulates multiple developmental processes. It accumulates in the root elongating endodermis, but how it moves into this cell le and the signi cance of this accumulation are unclear. Here, we identi ed a monophyletic clade of NPF transporters required for GA and abscisic acid (ABA) translocation. We demonstrate that NPF2.14 is a subcellular GA/ABA transporter, the rst to be identi ed in plants, facilitating GA and ABA accumulation in the root endodermis to regulate suberizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
(72 reference statements)
0
19
0
Order By: Relevance
“…The degradation of DELLA by GA in dark-grown roots releases these TFs and probably triggers transcriptional activation of numerous pathways independently of light. These may include the regulation of root architecture (Castro-Camba et al ., 2022), secondary xylem development, lignification (Wang et al, 2017) and endodermal suberin formation (Binenbaum et al ., 2023), but not cell elongation. Several DELLA-interacting TFs are involved in GA regulation of cell elongation (de Lucas et al ., 2008; Feng et al ., 2008; Gallego-Bartolome et al ., 2012; Chaiwanon & Wang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The degradation of DELLA by GA in dark-grown roots releases these TFs and probably triggers transcriptional activation of numerous pathways independently of light. These may include the regulation of root architecture (Castro-Camba et al ., 2022), secondary xylem development, lignification (Wang et al, 2017) and endodermal suberin formation (Binenbaum et al ., 2023), but not cell elongation. Several DELLA-interacting TFs are involved in GA regulation of cell elongation (de Lucas et al ., 2008; Feng et al ., 2008; Gallego-Bartolome et al ., 2012; Chaiwanon & Wang, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It was furthermore demonstrated that GA 12 derived in the roots plays a role in regulating the growth of shoots in response to temperature changes in Arabidopsis ( Camut et al 2019 ). Most recently, it was reported that two GA and ABA transporters (NPF2.12 and NPF2.13) are required for shoot-to-root GA 12 translocation to regulate endodermal root suberization (summarized below) ( Binenbaum et al 2023 ).…”
Section: Ga Transport Mechanismmentioning
confidence: 99%
“…Recent research has revealed that a subset of NPF proteins is required for the mechanisms behind long-distance GA transport from shoot to root and its developmental importance ( Binenbaum et al 2023 ). GA transport plays a critical role in suberin formation in the root.…”
Section: Ga Transport Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Jang et al (2023) illustrated that the ABA and GA balance is not an absolute factor in determining dormancy. Binenbaum et al (2023) revealed that GA is required for root suberization and that GA and ABA can act non‐antagonistically. However, ABA positively regulates dormancy induction and maintenance, while GA alleviates dormancy and promotes seed germination (Tuan et al 2018; Barreto et al 2020).…”
Section: Introductionmentioning
confidence: 99%